Enhanced Photocatalytic Activity of La3+ doped Bicrystalline Titania Prepared via Combustion method for the Degradation of Cationic dye Under Solar Illumination - Radhika R Nair; Mothi Krishna Mohan; Sunaja Devi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
La3+ doped TiO2 photocatalysts were successfully synthesized by combustion method in the presence of urea and were characterized by various physico-chemical techniques. Further, the photocatalytic performance of the synthesized catalysts was monitored by photocatalytic degradation of synthetic cationic dye-Methylene Blue (MB) under solar illumination. The bicrystalline phase of anatase and rutile was confirmed by X-ray diffraction analysis. Moreover, the transformation from anatase to rutile phase proceeds at a slower rate in the La3+ doped TiO2 catalysts. Effective separation of charge carriers, a synergistic effect in the bicrystalline framework of anatase and rutile, smaller crystallite size, and higher concentration of surface adsorbed hydroxyl groups helped these catalysts to show improved activity for the dye degradation.